2015
DOI: 10.7314/apjcp.2015.16.10.4215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Insulin Like Growth Facror-1 Genetic Polymorphism with Gastric Cancer Susceptibility and Clinicopathological Features

Abstract: Gastric cancer (GC) is one of the most common malignancies in the world. It is the first cause of cancer deaths in both sexes In Iranian population. Circulating insulin-like growth factor-one (IGF-1) levels have been associated for gastric cancer. IGF-1 protein has central roles involved in the regulation of epithelial cell growth, proliferation, transformation, apoptosis and metastasis. Single nucleotide polymorphism in IGF-1 regulatory elements may lead to alter in IGF-1expression level and GC susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…However, not all individuals exposed to these factors have developed GC, suggesting that genetic factors may play an important role in GC development. In recent years, some genes involved in GC risk have been reported, including microRNAs -146a, interleukin-17A (IL-17A), low molecular weight protein 2 (LMP2), LMP7, telomerase reverse transcriptase ( TERT ) and so on [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all individuals exposed to these factors have developed GC, suggesting that genetic factors may play an important role in GC development. In recent years, some genes involved in GC risk have been reported, including microRNAs -146a, interleukin-17A (IL-17A), low molecular weight protein 2 (LMP2), LMP7, telomerase reverse transcriptase ( TERT ) and so on [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all individuals exposed to such risk factors develop this disease, suggesting that genetic factors may contribute to its development. Indeed, many previous studies have reported that certain genes are involved in gastric cancer risk, includingmiR-146a, IL-17A, LMP2, LMP7, IGF1, and GSTM1 (Farahani et al, 2015;Hou and Yang, 2015;Ma et al, 2015;Wei et al, 2015;Zhang and Cui, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A Japanese study reported that two IGF1 SNPs (rs1520220 and rs2195239) were significantly associated with relapse-free survival in gastric cancer patients who had undergone curative gastrectomy [ 9 ]. In addition, an IGF1 gene polymorphism (rs5742612) was not associated with clinicopathological features in Iranian gastric cancer patients [ 18 ]. These data suggest that IGF- axis gene polymorphisms may be associated with gastric cancer progression, and that these associations may be modified by the cancer stage.…”
Section: Discussionmentioning
confidence: 99%